Rapid Automatized Picture Naming as a Proficiency Assessment for Endangered Language Contexts: Results from Wilamowice - Robert Borges (Journal of Communication and Cultural Trends, 2019)
This paper discusses the use of rapid automatized picture naming (RAN) in the assessment of proficiency among new speakers of endangered languages. Despite the fact that measuring proficiency among new speakers is crucial vis-à-vis the development of didactic materials and understanding language change, there are often a number of practical issues that reduce the practicality of traditional language evaluation methods. This paper investigates the potential of RAN assessments to provide a suitable indication of language proficiency by means of accuracy (ability to name pictures), speed (how quickly a verbal response is produced), and cognitive control (how well the speaker mediates cognitive load while performing the task). Results from RAN assessments administered among new speakers of Wymysorys, in concert with other data collection procedures, indicate that this type of task provides accurate insight into speakers’ proficiency. Latencies in the bilingual picture naming allow accurate insight into speakers’ proficiency as a function of the relative degrees of language entrenchment. However, increasing cognitive load during the assessment via speed of cue stimulus and frequently switching trial language showed no effect relative to the proficiency rank order established by naming accuracy and speed.